Analisis Pola Pengelolaan Keuangan pada Badan Layanan Umum Daerah - Masril Tua Rambe; Tigor Panuturi Tambunan; Nurlinda Nurlinda (Mahesa Research Center, 2023)
This article discusses the financial administration of Regional Public Service Agency (Badan Layanan Umum Daerah) and its alignment with the financial plan of the Regional Public Assistance Organization. The Regional Public Assistance Organization is a local government entity that provides assistance without prioritizing profit. Its management is governed by Regulation Number 1 of 2004 regarding State Storage Institutions and Unofficial Law Number 12 of 2019 concerning Territorial Monetary Administration. The topics covered include revenue, utilization, and funding of the Regional Public Assistance Organization. Revenue sources encompass administrative fees, collaborations, local government budgets (APBD), and others. Administrative rates are determined by unit costs and reserve profit. Tax systems consider maintenance, enhancement, purchasing power, and fairness. Despite financial management improvements enhancing governance effectiveness, deficiencies highlighted by the Supreme Audit Agency (Badan Pengkajian Unggul or BPK) regarding the financial administration of the Regional Public Assistance Organization underscore the need for development in the financial administration of the Regional Public Service Agency.